2018
DOI: 10.1029/2018tc004977
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Tomography of Eastern Tibet: Implications for the Tibetan Plateau Growth

Abstract: The eastern region of the Tibetan Plateau and surrounding regions have gentle to moderate topographic gradients, contrasting the steep margins in northern and southern Tibet. The mechanisms for plateau growth in eastern Tibet are uncertain so far. Here we present a new shear wave tomography model of the Tibetan Plateau derived from S wave traveltimes from teleseismic waveforms recorded by the dense ChinArray seismic network. The model reveals the deep structures beneath the eastern region of the Tibetan Platea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 83 publications
2
29
0
1
Order By: Relevance
“…Many previous studies of regional and teleseismic tomography have revealed 3‐D Vp variations beneath the SE Tibetan Plateau (e.g., Huang & Zhao, ; Huang, Wang, Xu, Wang, et al, ; Lei et al, ; Lei & Zhao, ; Li et al, ; Pesicek et al, ; Wei et al, , ; Zhang et al, ). All these results show similar first‐order features, that is, the high‐V body beneath the Yangtze craton and widespread low‐V zones beneath Indochina.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many previous studies of regional and teleseismic tomography have revealed 3‐D Vp variations beneath the SE Tibetan Plateau (e.g., Huang & Zhao, ; Huang, Wang, Xu, Wang, et al, ; Lei et al, ; Lei & Zhao, ; Li et al, ; Pesicek et al, ; Wei et al, , ; Zhang et al, ). All these results show similar first‐order features, that is, the high‐V body beneath the Yangtze craton and widespread low‐V zones beneath Indochina.…”
Section: Discussionmentioning
confidence: 98%
“…Lei and Zhao () determined a new model of teleseismic tomography beneath eastern Tibet using travel‐time residuals recorded at 280 permanent stations; they found widespread low‐V zones in the upper mantle and high‐V bodies in the MTZ and so proposed the existence of a big mantle wedge under eastern Tibet (Lei et al, ). Zhang et al () collected more data recorded at the portable seismic stations deployed by the ChinArray project and determined a 3‐D Vs model in eastern Tibet. They focused on different strengths of the lithosphere beneath the plateau (weak due to low velocity) and its adjacent regions (strong due to high velocity) and further discussed their implications for the plateau growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these differences, most studies suggest that fast velocities in the mantle beneath the Sichuan Basin show a deep cratonic root is present, a remnant of the South China Block (e.g., Y. Hu & Wang, 2018;Obrebski et al, 2012;F. Zhang et al, 2018).…”
Section: Deep Structure Of the Sichuan Basin And Surrounding Regionsmentioning
confidence: 99%
“…Hu & Wang, 2018;Huang & Zhao, 2006;Lei & Zhao, 2016;C. Li & van der Hilst, 2010;Obrebski et al, 2012;F. Zhang et al, 2018).…”
unclassified